2018
DOI: 10.1093/hmg/ddy218
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic variant in EPHB4 results in central conducting lymphatic anomaly

Abstract: Central conducting lymphatic anomaly (CCLA) is one of the complex lymphatic anomalies characterized by dilated lymphatic channels, lymphatic channel dysmotility and distal obstruction affecting lymphatic drainage. We performed whole exome sequencing (WES) of DNA from a four-generation pedigree and examined the consequences of the variant by transfection of mammalian cells and morpholino and rescue studies in zebrafish. WES revealed a heterozygous mutation in EPHB4 (RefSeq NM_004444.4; c.2334 + 1G>C) and RNA-Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 49 publications
0
91
0
Order By: Relevance
“…Though basic science has made significant progress in identifying molecular pathways and genes associated with CLAs, at the present time there are no specific gene defects that are diagnostic. However, the conference participants emphasized the need for continuing these studies and suggested the possibility of collecting tissue left over after clinical diagnoses for use in lymphatic research.…”
Section: Recommendationsmentioning
confidence: 99%
“…Though basic science has made significant progress in identifying molecular pathways and genes associated with CLAs, at the present time there are no specific gene defects that are diagnostic. However, the conference participants emphasized the need for continuing these studies and suggested the possibility of collecting tissue left over after clinical diagnoses for use in lymphatic research.…”
Section: Recommendationsmentioning
confidence: 99%
“…We performed whole exome sequencing on the patient together with his parents using samples of whole blood following protocols similar to those previously published . Variants were filtered against public variant databases (dbSNP, 1000 Genomes Project, NHLBI ESP6500SI, gnomAD, and Kaviar) and >5000 in‐house exomes.…”
Section: Case Reportmentioning
confidence: 99%
“…We performed whole exome sequencing on the patient together with his parents using samples of whole blood following protocols similar to those previously published. 9,10 Variants were filtered against public variant databases (dbSNP, 1000 Genomes Project, NHLBI ESP6500SI, gnomAD, and Kaviar) and >5000 in-house exomes. Subsequent gene prioritization was on basis of deleterious predication and biology relevance by referring to Online Mendelian Inheritance in Man, which did not reveal any pathogenic variants in other candidate genes, including genes residing in chromosome 2p16, which has been linked to the autosomal dominant form of Carney complex.…”
Section: Case Reportmentioning
confidence: 99%
“…However, CCBE1 variants are only found in 25% of suspected cases . Isolated or syndromic primary lymphedema has been associated with variants in 27 additional genes, including EPHB4, FLT4, FOXC2, GATA2, GJA1, GJC2, HGF, HRAS, IKBKG, ITGA9, KIF11, KRAS, PTPN11, PTPN14, RAF1, RASA1, SOS1, SOX18, VEGFC, CELSR1, EPHB4, FAT4, PIEZO1, RELN, RIT1, TSC1, TSC2 , and ADAMTS3 …”
Section: Introductionmentioning
confidence: 99%
“…4 Isolated or syndromic primary lymphedema has been associated with variants in 27 additional genes, including EPHB4, FLT4, FOXC2, GATA2, GJA1, GJC2, HGF, HRAS, IKBKG, ITGA9, KIF11, KRAS, PTPN11, PTPN14, RAF1, RASA1, SOS1, SOX18, VEGFC, CELSR1, EPHB4, FAT4, PIEZO1, RELN, RIT1, TSC1, TSC2, and ADAMTS3. [5][6][7] Hydrops fetalis is defined as excessive fluid collections within fetal cavities and extravascular compartments: skin edema, ascites, pleural or pericardial effusions, thickened placenta, and polyhydramnios. It represents the end stage of a variety of disorders.…”
Section: Introductionmentioning
confidence: 99%